A Call for Criticism - Rappaport, Alexander (project baikal, 2017)
Architectural criticism did not exist in the USSR. It did not exist in the history of architecture either. It can be observed neither in the preset-day West nor in Russia. The place of architectural criticism is occupied by architectural journalism. An ideal architectural criticism supposes that the authors and their critics should be equally developed within the sphere of the given culture. (In literature of the 19th century, Pushkin was a great poet and, at the same time, a great critic.) There have not been any great critics in architecture.
Keywords: architectural criticism; absence of architectural criticism; journalism; model of ideal architectural criticism; equality of development of the author and the critic